FORMULATION DEVELOPMENT AND DRUG RELEASE EVALUATION OF A TOPICAL GEL-SMEDDS CONTAINING VITAMIN E - Nguyen, Van Liet; Nguyen, Vinh Tri; Le, Van Lien; Nguyen, Minh Y; Thoi, Van Loc; Tran, Phuong Thuy; Nguyen, Ngoc Nha Thao (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Vitamin E, a potent antioxidant in dermo-cosmetics, faces limited skin penetration in conventional formulations due to its high log P, leading to stratum corneum accumulation and poor bioavailability. Self-Microemulsifying Drug Delivery Systems (SMEDDS), forming nanometer-sized droplets, show promise in enhancing drug permeability. Objective: To improve Vitamin E's transdermal permeability and bioavailability using a SMEDDS gel formulation. Materials and methods: A SMEDDS gel was developed with MCT oil, Tween 80, and Transcutol. Its in vitro membrane permeation was assessed using a Franz Diffusion Cell. Results:The gel-SMEDDS had comparable viscosity to the control, with a particle size of 188.9 nm (PDI = 0.272). It achieved a maximum diffusion of 34.6% after 240 minutes, significantly outperforming the control. Conclusion: The SMEDDS technique successfully produced a novel topical Vitamin E gel with improved bioavailability compared to conventional formulations.